The functional response and predatory ability of the reduviid Coranus fuscipennis Reuter (Heteroptera: Reduviidae)) fed on the rice meal moth Corcyra cephalonica (Stainton) - Lam, Truong Xuan; Lien, Nguyen Thi Phuong; Cuong, Nguyen Quang (Vietnam Journal of Biotechnology, 2020)
The reduviid Coranus fuscipennis Reuter (Heteroptera: Reduviidae) is an important predator for biological control the pests of vegetables in Vietnam. The functional response of the 2nd, 3rd, 4th, 5th nymphal instars and adult male and female of the predator C. fuscipennis to the larvae of rice meal moth Corcyra cephalonica (Stainton) (Lepidoptera: Pyralidae) was evaluated in laboratory conditions (temperature 30±2ºC; relative humidity 75±5%; and 14:10 h Light:Dark). The results show that the nymph and adult of C. fuscipennis responded to different densities of prey. They killed more number of prey at higher prey densities and less prey at lower prey densities that produced a curve linear type II functional response (Holling 1959). The maximum consumption was always found restricted when rearing the C. fuscipennis at high prey densities. The relationship between the predation rate of the C. fuscipennis and the prey densities was negative correlation (R is between 0.70 and 0.98), but between the number prey killed and the prey density is positive correlation. The searching time prey of the C. fuscipennis decreased when the prey densities increased that was confirmed by the negative correlation (R between 0.85 and 0.98). The reduviid C. fuscipennis bred by the C. cephalonica in laboratory and they can use for biological control some pests of vegetables (P rapae, S. litura and P. xylostella) in Vietnam.